Quality assurance in Asia-Pacific Universities : implementing massification in higher education - Neubauer, Deane E. (Cham, Switzerland : Palgrave Macmillan, [2017], 2017)
This edited volume examines the importance of quality issues in contemporary higher education systems in the Asia Pacific. Part One foregrounds relevant discussions of ‘quality’ within today’s globalized, interconnected, and complex higher education systems while Part Two focuses on selected universities in the Asia Pacific region. Chapter contributors discuss how quality issues and quality assurance mechanisms are implemented in their situation-specific systems. Part Three extends the research of higher education quality assurance in Hawaii Pacific University (HPU) and the diverse international student body in the Australian higher education system. The conclusion chapter discusses a typology of methods used by higher education systems in establishing effective quality assurance mechanisms.